The Correlation between Self-Efficacy and Subjective Norm and its effect on Handwashing Behavior among School Students in Coastal Area - Nazliansyah; Ashar Abilowo (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
The most effective method of preventing the transmission of diseases through hand is Handwashing. The objectives of study is to identify relationships between gender, availability of handwashing facilities, perception of self-efficacy of hand washing, subjective norm and hand washing behavior among school students in coastal area. The design of the study is a cross-sectional research. The method this article use is the multistage sampling technique was used for the sampling method in this study. First stages, the researcher used purposive sampling to identify the seven Public Elementary Schools in the coastal area of Belitung District. Further, the proportionate sampling and random sampling technique were employed in this study. The results showed 11.3% the students were not proper in handwashing. Regarding of self efficacy, the study also revealed that self efficacy was related to handwashing practice among school students in the coastal area. The subjective norm (?² =4.459, p < .05) also related to hand washing practice among school students. The conclusion is the specific intervention can be developed by health care provider using method of subjective norm and self efficacy promotion to motivate handwashing practice among school students in the coastal area.